2016
DOI: 10.1017/s0031182016001190
|View full text |Cite
|
Sign up to set email alerts
|

Hybridizations within the GenusSchistosoma: implications for evolution, epidemiology and control

Abstract: Hybridization of parasites is an emerging public health concern in our changing world. Hybridization and introgression in parasites and pathogens can have major impacts on the host and the epidemiology and evolution of disease. Schistosomiasis is a Neglected Tropical Disease of profound medical and veterinary importance across many parts of the world, with the greatest human burden within sub-Saharan Africa. Here we review how early phenotypic identification and recent confirmation through molecular studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
163
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 133 publications
(234 reference statements)
3
163
0
Order By: Relevance
“…The importance and the frequency of hybridization in infectious agents are certainly underestimated, and very little attention has been given so far to the role of gene introgression on infectious disease emergence, spread and control [11]. In the genus Schistosoma, latest reports have revealed that hybrids are frequent throughout West Africa, and are already a real concern for human health [5,6]. Nevertheless, it is the first time that a hybrid schistosome is involved in a large-scale outbreak in Europe [8,12,13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance and the frequency of hybridization in infectious agents are certainly underestimated, and very little attention has been given so far to the role of gene introgression on infectious disease emergence, spread and control [11]. In the genus Schistosoma, latest reports have revealed that hybrids are frequent throughout West Africa, and are already a real concern for human health [5,6]. Nevertheless, it is the first time that a hybrid schistosome is involved in a large-scale outbreak in Europe [8,12,13].…”
Section: Resultsmentioning
confidence: 99%
“…Hybridizations between schistosomes have already been identified: (i) between different human-specific schistosome species, (ii) between different animal-specific schistosome species, (iii) and between human-specific and animal-specific schistosomes species [6]. These latter hybrid forms are particularly alarming because they raise the possibility of the emergence of new zoonotic parasitic strains, introducing an animal reservoir, and therefore greatly hampering our ability to properly control the life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The hybridization of closely related Schistosoma species has already been demonstrated in the laboratory [23], as well as in nature [8]. Nevertheless, hybridization between two major causative agents of intestinal and urinary schistosomiasis in Africa, Schistosoma mansoni and S. haematobium, has rarely been described [20] and was very recently observed in a patient originated from Côte d'Ivoire [19]. Hybridization between these two species is very surprising due to the high phylogenetic distance between them [15].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing array of examples of naturally occurring hybridizations between Schistosoma species across sub‐Saharan Africa (reviewed in Léger & Webster, ). Of particular interest in terms of parasite evolution, epidemiology and control is the confirmation of widespread viable hybridizations between the human schistosome species Schistosoma haematobium and the livestock schistosome species S. bovis and/or S. curassoni in West Africa (Huyse et al., ; Webster et al., ), and between S. haematobium and the livestock schistosome species S. mattheei in Southern Africa (De Bont, Vercruysse, Southgate, Rollinson, & Kaukas, ; Vercruysse et al., ).…”
Section: Introductionmentioning
confidence: 99%